Business Strategies for Improving Small-Scale Rice Processors’ Performance: Case Study of Kogi State - Nafiu, Akeem Tunde; Hassan, Olanrewaju Makinde; Egwu, Emmanuel Makoji (International Journal of Economics, Management and Accounting, 2023)
This study aimed at investigating the imperatives of business strategies for small-scale rice processors’ improved performance in Kogi State, Nigeria. The study used Cronbach coefficient alpha for reliability test, multistage sampling technique, and descriptive statistics, Principal Component Analysis (PCA) Logit regression and Multiple Regression Models, for data analysis. It was found that lack of sufficient resources has a negative relationship with the low cost strategy adoption, growth strategy adoption, value-chain strategy adoption and differentiation strategy adoption. Findings further show the significant effects of these strategies on the profitability of small-scale rice processors (SRP) in Kogi State. The study was restricted to Kogi State, considering small-scale rice processors. Large scale rice processors may not benefit from the study. Its sample size was limited based on its scope. The study is useful to SRPs in terms of the adoption of single, multiple or combination of business strategies. Findings of the present study will stimulate adoption of effective agri-business strategies that can improve profitability of SRPs. The research is new, novel and enhances SRP business practice.